2019
DOI: 10.1177/1369148119866086
|View full text |Cite
|
Sign up to set email alerts
|

A pessimistic liberalism: Jacob Talmon’s suspicion and the birth of contemporary political thought

Abstract: Discussions of liberalism as a political ideology often focus on the progressive, civilisational, and triumphalist ideologies of liberal thinkers. Scholarly work on liberal empire situates these issues in the context of colonialism, and contemporary discussions of liberal world order devote much intellectual space to optimism about liberalism. Scholars have spent much less time connecting liberalism to deep cynicism and suspicion. This article, in focusing on what I term a ‘pessimistic liberalism’, fills this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…On the other hand, we find that liberals were more sad and pessimistic, but also had higher anticipation and higher bias of fairness than conservatives. Previous work has related liberal thinking to more suspicion, pessimism and cynicism from a political science perspective (Tatum 2019), andGraham et al (2009) showed that liberals have greater endorsement and use of the fairness foundations.…”
Section: Heterogeneity Of Emotional and Moral Reactionsmentioning
confidence: 99%
“…On the other hand, we find that liberals were more sad and pessimistic, but also had higher anticipation and higher bias of fairness than conservatives. Previous work has related liberal thinking to more suspicion, pessimism and cynicism from a political science perspective (Tatum 2019), andGraham et al (2009) showed that liberals have greater endorsement and use of the fairness foundations.…”
Section: Heterogeneity Of Emotional and Moral Reactionsmentioning
confidence: 99%